1967
DOI: 10.1152/ajplegacy.1967.212.6.1469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased systemic venous pressure on lymph pressure and flow

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…As shown in Table 1, there generally seems to exist a threshold level in the outflow venous pressure above which thoracic duct flow decreases significantly. In the experiments inserting a catheter in the thoracic duct or in the efferent duct of the caudal mediastinal lymph node, such a threshold has also been observed when raising the outflow level of the catheter (Cole, Witte, Kash, Rodger, Bleisch & Muelheims, 1967;Szab o & Magyar, 1967;Drake et al 1985). In experiments using the interposed cannula in the thoracic duct (W egria et al 1963), a threshold was, however, not observed in anaesthetized dogs.…”
Section: Effect Of Outflow Venous Pressurementioning
confidence: 97%
“…As shown in Table 1, there generally seems to exist a threshold level in the outflow venous pressure above which thoracic duct flow decreases significantly. In the experiments inserting a catheter in the thoracic duct or in the efferent duct of the caudal mediastinal lymph node, such a threshold has also been observed when raising the outflow level of the catheter (Cole, Witte, Kash, Rodger, Bleisch & Muelheims, 1967;Szab o & Magyar, 1967;Drake et al 1985). In experiments using the interposed cannula in the thoracic duct (W egria et al 1963), a threshold was, however, not observed in anaesthetized dogs.…”
Section: Effect Of Outflow Venous Pressurementioning
confidence: 97%
“…(20) is that the lymph flow is sensitive to the central venous pressure (P RA ). Although there are a number of observations that suggest that lymph flow is sensitive to thoracic duct pressure [28,118-121] and systemic venous pressure [122,123], these results are indirect and not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) In addition, the elevated venous pressure resists the lymphatic inflow. 8,9) Blalock and Burwell have demonstrated the development of increased pressure and dilatation in the thoracic duct in their experiments on the hemodynamics of constrictive pericarditis. 10) It has been shown in animal studies that, in the presence of normal venous pressure, even when the thoracic duct is ligated, the development of chylous ascites is prevented by collaterals between the lymphatic and systemic circulations.…”
Section: A B Discussionmentioning
confidence: 99%